QUANTITATIVE DETERMINATION OF AMLODIPINE FROM CACO-2 CELL MONOLAYERS BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY–MASS SPECTROMETRY/MASS SPECTROMETRY - Logoyda, Liliya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple, rapid high-performance liquid chromatography–mass spectrometry/mass spectrometry (MS/MS) method was developed for the determination of amlodipine from confluent Caco-2 monolayers and from aqueous solution. Methods: Chromatography was achieved on Discovery C18, 50×2.1 mm, 5 μm column. Samples were chromatographed in a gradient mode (eluent A [acetonitrile-water-formic acid, 5:95:0.1 v/v], eluent B [acetonitrile-formic acid, 100:0.1 v/v]). The initial content of the eluent B is 0%, which increases linearly by 1.0 min to 100% and to 1.01 min returns to the initial 0%. The mobile phase was delivered at a flow rate of 0.400 ml/min into the MS electrospray ionization chamber. The sample volume was 5 μl. Results: Under these conditions, amlodipine was eluted at 1.61 min. According to the Caco-2 test results, amlodipine appeared to have moderate to high permeability. Recovery value for amlodipine is 52.33%. Caco-2 permeability values for amlodipine are in agreement with BCS Class I classification for these drugs and their known high bioavailability in humans. Conclusion: A new rapid method was developed for the determination of amlodipine from confluent Caco-2 monolayers and from aqueous solution. Acquired results demonstrate that proposed strategy can be effortlessly and advantageously applied for the examination of amlodipine from Caco-2 cell monolayers.